Islamic schools in modern Turkey : Faith, Politics, and Education - Ozgur, Iren (New York, Cambridge University Press, 2012)
"An analysis of Imam-Hatip schools in Turkey and how they contribute to the Islamization of the country at both the high and grassroots levels of politics"--
Machine generated contents note: 1. Imam-Hatip schools within a secular state; 2. Accumulating and exhibiting habitus; 3. Agents of political socialization: influences in the communities; 4. Imam-Hatip schools, their communities, and Islamist politics; 5. Imam-Hatip schools, their communities, and Islamist civil society organizations; 6. International interest and conclusions.
Keywords: Islamic religious education; Islam and state